2020
DOI: 10.1186/s40594-020-00231-6
|View full text |Cite
|
Sign up to set email alerts
|

Science identity and metacognitive development in undergraduate mentor-teachers

Abstract: Background: A growing part of the efforts to promote student engagement and success in undergraduate STEM are the family of Student Support and Outreach Programs (SSOPs), which task undergraduate students with providing support and mentoring to their peers and near-peers. Research has shown that these programs can provide a variety of benefits for the programs' recipients, including increased academic achievement, satisfaction, retention, and entry into STEM careers. This paper extends this line of inquiry to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…Third, students in all three groups developed more positive interest and identity toward STEM, and students in the mentorship group particularly developed much stronger interest and identity than the other two groups that did not involve mentors (H3, H4, and H5). These results are supported by studies that suggest that engaging role models or mentors in STEM learning can better cultivate students' STEM interest and identity (Honey et al, 2014;Pinkard et al, 2017;Ladeji-Osias et al, 2018;Musavi et al, 2018;Huvard et al, 2020). These findings also imply that positive interest and identity toward STEM are developed in a social context (Renninger and Hidi, 2011;Goos and Bennison, 2019).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Third, students in all three groups developed more positive interest and identity toward STEM, and students in the mentorship group particularly developed much stronger interest and identity than the other two groups that did not involve mentors (H3, H4, and H5). These results are supported by studies that suggest that engaging role models or mentors in STEM learning can better cultivate students' STEM interest and identity (Honey et al, 2014;Pinkard et al, 2017;Ladeji-Osias et al, 2018;Musavi et al, 2018;Huvard et al, 2020). These findings also imply that positive interest and identity toward STEM are developed in a social context (Renninger and Hidi, 2011;Goos and Bennison, 2019).…”
Section: Discussionsupporting
confidence: 54%
“…Introducing role models or mentors in STEM education can enhance students’ STEM interest and identity development ( Honey et al, 2014 ; Nelson et al, 2017 ; Huvard et al, 2020 ). In mentorship programs, students often engage in three types of interactions with mentors: shareability, tangibility, and aesthetic ( Tofel-Grehl et al, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indirect effect 3 was metacognitionchemistry learning burnoutchemistry learning flowchemistry identity (the variable processing is the same as in the previous table ). This journal is © The Royal Society of Chemistry 2022 (Hazari et al, 2010;Huvard et al, 2020). Although studies have demonstrated that metacognition could affect identity formation (Welsh and Schmitt-Wilson, 2013), there is no direct empirical evidence that metacognitive awareness has a positive effect on students' science identity, such as their chemistry identity.…”
Section: The Relationship Between Metacognition and Chemistry Identitymentioning
confidence: 99%
“…In science education, there has been increased concern regarding science identity development. Science identity is seen as an important construct that positively influences learners' academic decisions, academic achievement, and persistence in the major (Perez et al, 2014), and it is regarded as a critical outcome of experiential science, technology, engineering, and mathematics (STEM) programs (Huvard et al, 2020). Because chemistry is well accepted as a compulsory introductory subject within STEM discipline fields (Gonzalez and Paoloni, 2015), researchers have particularly highlighted chemistry identity development in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…For example, talking about science with friends and family (Dou et al, 2019) and the influence of parents and teachers (Jackson & Suizzo, 2015; Stitt Richardson et al, 2019) during childhood are associated with stronger STEM identity. In college, students’ interactions with STEM faculty with whom they have a relationship are also positively related to STEM identity (Hurtado et al, 2011; Nadelson et al, 2017) as are formal mentoring relationships with faculty (Piatt et al, 2019; Robnett et al, 2020) and serving as a peer mentor (Huvard et al, 2020). Informal and formal interactions with peers are also positively associated with STEM identity (Espinosa, 2011).…”
Section: Cti and Stem Identitiesmentioning
confidence: 99%